УМУМТАЪЛИМ ФАНЛАРИНИ ТАДБИРКОРЛИККА ЙЎНАЛТИРИБ ЎҚИТИШНИНГ ЭДУКОЛОГИК ИМКОНИЯТЛАРИ - Мирзакаримова, М.М. (SCIENCE and SOCIETY, 2020)
The article presents opinions and comments on the ethic-potential entrepreneurship-oriented teaching of general subjects in the development of the activities of a well-rounded person and qualified professionals in the process of socio-economic production.